Parentage assignment in black soldier fly (Hermetia illucens) using genotyping-by-sequencing - Dufresne, Guyllaume; Bolduc, Catherine; Warburton, Christopher; Vandenberg, Grant; Deschamps, Marie-Hélène; Alnahhas, Nabeel (Frontiers in Genetics, 2025)
Genetic selection to optimize economically important traits in black soldier flies (BSF), a major species in the insects as food and feed industry, continues to gain interest. Tracking pedigrees is a prerequisite for generating genetic progress while conserving the genetic variability of traits under selection. However, this is not currently feasible in mass reared insects like BSF. As an alternative, this study identified SNPs informative for parentage assignment (PA) in a commercial and laboratory colony of BSF using genotyping-by-sequencing (GBS). We first established an experimental population of 12 BSF families per colony by randomly mating flies within each family over three generations. DNA was then sequenced from mated pairs and two larvae per pair per generation (n = 288 samples). After SNP calling and filtering, we generated four high-quality SNP subsets containing 192, 118, 72, and 51 SNPs, respectively. PA was conducted using a likelihood-based method across simulated inbreeding rates from 0% to 100%. Compared to known parents, PA accuracy reached 100% across all SNP subsets and inbreeding rates. However, assignment confidence as measured by the log-likelihood (LOD) score decreased significantly as the number of SNPs decreased, though inbreeding had no significant effect on LOD scores. High-confidence assignments to either male or female parents required all 192 SNPs, whereas high-confidence assignments to parent pairs were possible with 118 or 192 SNPs. The identified SNPs provide a valuable resource for developing low-density panels to implement pedigree-based selection and to manage genetic diversity, thereby supporting the development of breeding programs in BSF.